MODIFIED GERAGHTY TYPE VIA SIMULATION FUNCTIONS - Bunpatcharacharoen, P.; Kitcharoen, W. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2023)
We explore the Geraghty contraction through a simulation function, elucidating certain conditions for the existence and uniqueness of coincidence points for multiclass mappings involving the Geraghty function in metric spaces. The results presented in this work are consistent with those found in existing literature.